Sea Ice Index - Multimission ... : SIIN ... - OSI SAF; EUMETSAT SAF On Ocean And Sea Ice (EUMETSAT SAF on Ocean and Sea Ice, 2020)
The Sea Ice Index is a climate indicator of sea-ice coverage. The index covers both the sea-ice extent and area over the last 40+ years and is continuously updated to present time. It consists of an updated series of graphs (.png) visualising the trends and evolution of sea ice at hemispheric, global and regional scales. In addition, the data files (.txt and .nc) are available for users who are interested in analysing and plotting the data themselves. The Sea Ice Index is derived from the OSI SAF Global Sea Ice Concentration data, with R&D input from ESA CCI. ...